POLA PENGGUNAAN BALANCED SCORCARD (BSC) PADA INDIKATOR KINERJA UTAMA (IKU) UNIVERSITAS ISLAM NEGERI (UIN) SYARIF HIDAYATULLAH JAKARTA - Fitriadi (2020)
The research problems about phenomena of the difficulty in seeing performance achievements and performance measurements at State Islamic University (UIN) Syarif Hidayatullah Jakarta. The UIN Syarif Hidayatullah Jakarta has difficulty making decisions in performance management, because before using the KPI, Its used budget management in performance appraisal and measurement. Performance can only be seen in budget realization. This research uses a qualitative method of field study with a phenomenological approach. Research objects are the experiences of the use of the Balanced Scorecard (BSC) pattern on the KPI of the UIN Syarif Hidayatullah Jakarta in 2018. After its existence of the Main KPI using the BSC, The phenomenon that can be seen is UIN Syarif Hidayatullah Jakarta has been able to see performance appraisals and performance measures from a balanced card of financial perspective, customer perspective, learning perspective, growth, internal business process perspective. The results of the KPI are taken into consideration for performance evaluation by stakeholders at UIN Syarif Hidayatullah Jakarta in achieving the organization's vision. This performance appraisal and performance measurement can serve as a reference for performance achievements for Higher Education Rankings at the national and international level, Government Institution Performance Accountability Report (LAKIP), Strategic Plan (Renstra) and Campus Development Master Plan (RIBKA) or Milestones by looking at indicators, targets and size of the report